PERANCAGAN APLIKASI DASHBOARD DATA MASYARAKAT MISKIN DI DESA MACANG SAKTI KABUPATEN MUSI BANYUASIN - Deni Nurdiansyah; Joni Karman; Muhammad Nur Alamsyah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Often the data from the field is not synchronized with the data processed by the system because there are no applications that can manage data for the poor so that inaccurate results are obtained. At this time making reports on data for the poor are still using Microsoft Word. The report was submitted to the Head of Macang Sakti Village, Musi Banyuasin Regency. This can result in the recipient of the report being less effective. If an existing report disappears somewhere, it can result in the village government being obliged to make another report that has disappeared. The reporting system by implementing a mobile web-based dashboard application appears a way out for current reporting problems. This application is made using php and database. Become a medium for the village government in reporting data on the poor to the Village Head of Macang Sakti providing information about data on the poor in Macang Sakti Village.